Inventory of Anura in Sarasah Salisikan Waterfall Area, Batang Anai, Padang Pariaman Regency, West Sumatra - Saputra, Yogi; Nugraha, Fitra; Satria, Rijal; Atifah, Yusni (Jurnal Serambi Biologi, 2023)
The purpose of this study was to collect data on amphibians of the Anura order in the Sarasah Salisikan waterfall area, Batang Anai District, Padang Pariaman Regency, West Sumatra. Because this area will be developed into a tourist area by the local nagari government and also plantation activities around the waterfall which will affect the number of species that inhabit this area. This study used the VES (Visual Encounter Survey) method, which is based on direct encounters with specimens in the field. The research was conducted in November-December 2022, the research results found a total of 9 species consisting of 5 families. This research area will be a place to conduct similar research in the future. Keywords :Inventory, Anura, Sarasah Salisikan Water fall, Batang Anai, West Sumatera